2008
DOI: 10.1152/jn.00784.2007
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Skylight Navigation in Insects: Model and Electrophysiology of e-Vector Coding by Neurons in the Central Complex

Abstract: Sakura M, Lambrinos D, Labhart T. Polarized skylight navigation in insects: model and electrophysiology of e-vector coding by neurons in the central complex. J Neurophysiol 99: 667-682, 2008. First published December 5, 2007 doi:10.1152/jn.00784.2007. Many insects exploit skylight polarization for visual compass orientation or course control. As found in crickets, the peripheral visual system (optic lobe) contains three types of polarization-sensitive neurons (POL neurons), which are tuned to different (ϳ60°d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 45 publications
5
95
0
Order By: Relevance
“…The polarity of CL1a cells is unique among columnar neurons in the locust central complex and suggests signaling from dendrites in the CBL to axonal outputs in the PB. Presumed input arborizations of CL1a neurons are concentrated in dorsal layers of the CBL, coinciding with layers served by TL2 tangential neurons, which are regarded as the dominant polarization-vision input to the CBL and have been also characterized in crickets (Sakura et al, 2008). In contrast, CL1b-d cells are likely to receive input in the PB and convey this information to the CBL.…”
Section: Connecting the Cbl With The Pbmentioning
confidence: 99%
“…The polarity of CL1a cells is unique among columnar neurons in the locust central complex and suggests signaling from dendrites in the CBL to axonal outputs in the PB. Presumed input arborizations of CL1a neurons are concentrated in dorsal layers of the CBL, coinciding with layers served by TL2 tangential neurons, which are regarded as the dominant polarization-vision input to the CBL and have been also characterized in crickets (Sakura et al, 2008). In contrast, CL1b-d cells are likely to receive input in the PB and convey this information to the CBL.…”
Section: Connecting the Cbl With The Pbmentioning
confidence: 99%
“…In locusts, crickets, and monarch butterflies skylight polarization signals are processed in the CC (Sakura et al, 2008;Heinze and Reppert, 2011;Homberg et al, 2011). In desert locusts, a compass-like representation of zenithal E-vector tunings in the PB suggests that the CC plays a role as an internal sky compass (Heinze and Homberg, 2007).…”
Section: Visual Integration In the CCmentioning
confidence: 99%
“…At the neuronal level, polarization vision pathways in the brain have been studied most extensively in locusts and crickets (Labhart and Meyer, 2002;Homberg, 2004). In these insects, the central complex is a major processing stage for polarized light (Vitzthum et al, 2002;Homberg, 2007, 2009;Sakura et al, 2008;). showed that polarization-sensitive (POL-) neurons connect the central complex to the lateral accessory lobes and the posterior protocerebrum, brain areas that are innervated by intersegmental neurons (Williams, 1975;Strausfeld and Seyan, 1985;Okada et al, 2003).…”
Section: Introductionmentioning
confidence: 99%